DEVELOPMENT AND OPTIMIZATION OF ENZALUTAMIDE-LOADED SOLID LIPID NANOPARTICLES USING BOX–BEHNKEN DESIGN - TARAKA SUNIL KUMAR K; MOHAN VARMA M; RAVI PRAKASH P (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The primary motive behind this investigation is to develop and optimize the solid lipid nanoparticles formulation of enzalutamide for the effective drug delivery. Materials and Methods: The formulation variables were optimized using design of experiments. Box–Behnken design was used for the study and the results were analyzed using response surface methodology. The prepared nanoformulation was characterized for particle size, zeta potential, surface morphology, X-ray diffractometry (XRD), in vitro drug release kinetics, and stability study. Results: The influence of formulation variables, drug-to-lipid ratio, concentration of phosphatidylcholine, and concentration of poloxamer 188 were evaluated by regression analysis. The optimized formulation (F3) was found to have the minimum particle size (253 nm) with maximum entrapment efficiency (89.72%) and drug loading (23.84%). From SEM studies, the data showed a spherical shape for enzalutamide nanoparticles with uniform and relatively narrow particle distribution. From XRD examines, it is demonstrative that the drug was not in crystalline form in nanoformulation when compared with pure drug. In vitro release studies disclosed that maximum cumulative drug release was attained by F3 (99.72%) in controlled manner. The optimized formulation of enzalutamide followed zero-order release kinetics with a strong correlation coefficient (R2 = 0.9994). Conclusion: The nanoformulation prepared under optimized conditions is in concurrence with the expected results. The SLN formulation can be used as a potential carrier for the effective delivery of enzalutamide.